An important role of decomposing wood for soil environment with a reference to communities of springtails (Collembola) - Čuchta, Peter; Kaňa, Jiří; Pouska, Václav (Environmental monitoring and assessment, 2019)
Present study focused on how the presence of decaying wood affects soil environment including its biota. The study was carried out in the montane spruce forest, disturbed by wind and bark beetles in Trojmezná Mt. of the Bohemian Forest in the Czech Republic. According to the results, presence of decomposing wood influenced soil environment in terms of its chemical properties by increasing soil pH and total carbon content significantly in soil below the trunks compared with soil from further distance. Decomposing wood did not affect total density and species richness of Collembola, but it had a significant influence on species composition and some species were more abundant in soil right below the trunks whereas others preferred soil environment further from them. Finally, significant relations, both positive and negative, were recorded between some Collembola species and ammonium. Thus, this substance might play a role of a volatile attractant in soil environment.
Keywords: houby; monitorování životního prostředí; Soil Microbiology; Saprotrophic fungi; Picea; Wood; Česká republika; Environmental Monitoring; Ammonium content; Czech Republic; Fungi; Collembola; půda; zvířata; půdní mikrobiologie; lesy; dřevo; členovci; Decomposing wood; Community data; Decay; smrk; Arthropods; Soil; Forests; Animals